3(x-2)+(-3)=4(x+1)

Simple and best practice solution for 3(x-2)+(-3)=4(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+(-3)=4(x+1) equation:


Simplifying
3(x + -2) + (-3) = 4(x + 1)

Reorder the terms:
3(-2 + x) + (-3) = 4(x + 1)
(-2 * 3 + x * 3) + (-3) = 4(x + 1)
(-6 + 3x) + (-3) = 4(x + 1)
-6 + 3x + -3 = 4(x + 1)

Reorder the terms:
-6 + -3 + 3x = 4(x + 1)

Combine like terms: -6 + -3 = -9
-9 + 3x = 4(x + 1)

Reorder the terms:
-9 + 3x = 4(1 + x)
-9 + 3x = (1 * 4 + x * 4)
-9 + 3x = (4 + 4x)

Solving
-9 + 3x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-9 + 3x + -4x = 4 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-9 + -1x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + -1x = 4 + 0
-9 + -1x = 4

Add '9' to each side of the equation.
-9 + 9 + -1x = 4 + 9

Combine like terms: -9 + 9 = 0
0 + -1x = 4 + 9
-1x = 4 + 9

Combine like terms: 4 + 9 = 13
-1x = 13

Divide each side by '-1'.
x = -13

Simplifying
x = -13

See similar equations:

| r(2x+3)=0.5x+1 | | b^2=-2+3b | | 20x+12y=344 | | 2(5z-1)-5(z+9)=2(z+1) | | 18-3x=2+2x | | 9n^2=-1 | | 5(3/2)+3(4/2)= | | 41+a=10 | | 2xy-3y+6=0 | | 3x-5=24+7 | | (3x-18)=105+99 | | 5.4+-9.7= | | 2/3x-1/2=3/4 | | 29n=-377 | | 2(x+3)=4*-3 | | (2x-4)2=36 | | 4(6x-31)=5-4(x+3) | | 7(4x+8)-6=-106 | | 3v^2+12v=-8 | | 7x-4=-2x+2+9x-5 | | 9(x+1)=25+6 | | -2(2-x)=-8+6x | | 11+2n=9 | | -7(1x-6)=-14 | | 57=5x-3 | | -3(5m+4)-3(m-7)= | | y-12=89 | | 5x^2+11xy+2y^2=0 | | mx=-nx+p | | 9x-15=9(x-13) | | 38=8+6(y+2) | | 136=-17b |

Equations solver categories